Emerging and imported infections in the region – what's bothering us today?. (July 2013) - Teo, D.
<x xml:space="preserve">Abstract</x> An emerging infection is defined as one that has appeared in a population for the first time, or that may have existed previously but is rapidly increasing in incidence or geographic range. The Asia Pacific region, with 30% of global population, has a reputation as a hot spot for emerging infections. The emergence of severe acute respiratory syndrome exactly 10 years ago dramatically transformed individual and national awareness and capabilities for identifying and responding to regional emerging infectious threats. The impact of emerging infections on the blood supply may be direct through the potential for transmission through transfusion, the effect on blood donor attendance and eligibility and the effect on blood demand. There is a need for constant surveillance and the capacity to identify, assess and manage risks to the blood supply. In recent years, the strengthening of regional and international partnerships and the development of new risk assessment tools has improved our ability to respond to infectious threats. Nonetheless, the volatile and ever‐changing nature of emerging infections will remain a constant challenge to the vigilance and response capabilities of the transfusion medicine community.